Feminist legal theory : (Westview Press, 1991)
Our understanding of the law and its potential for reforming social and political norms was dramatically reshaped in the 1980s by the intellectual movement known as feminist legal theory. For students of the law, for anyone interested in women's issues, for experienced scholars, and for newcomers, Feminist Legal Theory is not just essential reading but an enduring reference work